Basic course of mathematics created by overlapping methodology of topics - Burgis, Bronislovas (Lietuvos matematikos rinkinys, 2023)
How to decrease the redundancy in the textbooks of mathematics? How to improve the math curricula? Overlapping of topics is the source for improvement. Proposals of this article are based on the experience acquired in the process of writing a book of math examples for high school and university students.